DI-077 A pharmaceutical care programme to improve pain management in patients with advanced prostate cancer. (25th February 2017) - Garcia, MDP; Villacañas, MV; Laso, E; Corral, A; Otero, MJ; Sanchez, A
Abstract : Background: Pain is a frequent symptom with many types of cancer. In 80–85% of patients with metastatic prostate cancer (MPC), the cancer spreads to the bone, which causes pain, pathologic fractures or spinal cord compression. Purpose: To develop a pharmaceutical care programme and to analyse the prevalence of pain in patients with MPC who attended the outpatient area of the hospital pharmacy. Material and methods: A literature search in several databases was conducted (Pubmed, Medline and Google Scholar) for a review of pain in patients with MPC. We also consulted the websites of the National Cancer Institute and other cancer organisations. The Wisconsin Brief Pain Questionnaire was selected for characterising the types and degree of pain that patients experienced. A diary to be distributed to patients to record their pain in terms of degree, duration and analgesic treatment, and an educational pamphlet about oncologic pain that included advice on how to deal with the pain and better understand its symptomatology, were developed. Follow-up of patients with MPC who began receiving treatment with abiraterone or enzalutamide from the hospital pharmacy from January to July 2016 was performed. They completed a questionnaire designed to evaluate the type of pain they were experiencing at their initial visit and at subsequent visits. They were given the diary and an informational pamphlet. Results: The programme began with 38 patients, of whom 56% presented with bone metastases. From the questionnaires they completed at each visit, it was observed that 35% reported pain. The most common analgesic treatment used was NSAIDs (36%) or NSAIDs plus opioids (29%). The materials patients received improved characterisation of their pain and served as a psychological support, basically through understanding that pain was a frequent symptom of their illness and one that could be treated more effectively. Conclusion: A high prevalence of pain in patients with MPC was identified which indicates that analgesic treatment is often inadequate. Creating pharmaceutical care programmes may contribute to better pain evaluation and treatment, and better support for patients. References and/or acknowledgements: The author would like to thank the pharmacists who supported this study. No conflict of interest